2002
DOI: 10.1016/s0006-3495(02)75292-2
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State NMR Determination of Sugar Ring Pucker in 13C-Labeled 2′-Deoxynucleosides

Abstract: The H3'-C3'-C4'-H4' torsional angles of two microcrystalline 2'-deoxynucleosides, thymidine and 2'-deoxycytidine.HCl, doubly (13)C-labeled at the C3' and C4' positions of the sugar ring, have been measured by solid-state magic-angle-spinning nuclear magnetic resonance (NMR). A double-quantum heteronuclear local field experiment with frequency-switched Lee-Goldberg homonuclear decoupling was used. The H3'-C3'-C4'-H4' torsional angles were obtained by comparing the experimental curves with numerical simulations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 50 publications
(72 reference statements)
2
13
0
Order By: Relevance
“…Investigations on sugar conformation (see Material and Methods) show that South conformers largely prevail in purine nucleotides of the dodecamers, but observable TOCSY H1′-H4′ cross-peaks indicate the presence of North or East conformers on 17 sugars of pyrimidine nucleotides (C7, C15 and C19 in Oligo 1; C2, C4, T5, C8, C10 and T16 in Oligo 2; C4, T6, C10 and T16 in Oligo 3; C9, C11, C15 and C23 in Oligo 4). Such a feature is thus typically seen on cytosine sugars, in line with previous ab initio quantum mechanical predictions ( 69 ) and subsequent observations ( 13 , 29 , 46 , 70 73 ). Nevertheless, steps with sugars undergoing South ↔ North or East transitions do not stand out in the correlations shown in Figure 4 .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Investigations on sugar conformation (see Material and Methods) show that South conformers largely prevail in purine nucleotides of the dodecamers, but observable TOCSY H1′-H4′ cross-peaks indicate the presence of North or East conformers on 17 sugars of pyrimidine nucleotides (C7, C15 and C19 in Oligo 1; C2, C4, T5, C8, C10 and T16 in Oligo 2; C4, T6, C10 and T16 in Oligo 3; C9, C11, C15 and C23 in Oligo 4). Such a feature is thus typically seen on cytosine sugars, in line with previous ab initio quantum mechanical predictions ( 69 ) and subsequent observations ( 13 , 29 , 46 , 70 73 ). Nevertheless, steps with sugars undergoing South ↔ North or East transitions do not stand out in the correlations shown in Figure 4 .…”
Section: Resultssupporting
confidence: 89%
“…An earlier analysis of a large data set of X-ray structures showed that in both free and bound DNA the slide, roll and twist are correlated to various degrees, depending on the dinucleotidic sequence ( 5 ). Several other studies, based on high resolution X-ray structures, revealed intimate structural couplings between the phosphate group states, sugar conformations, inter base pair parameters, base pair displacement (X-disp) and groove dimensions ( 6 13 ). The backbone conformations in free B-DNA consist of two states, BI and BII, originally defined by the conformations of the torsion angles ε and ζ trans/g- in BI (ε − ζ ∼ −90°) and g-/trans in BII (ε − ζ ∼ +90°) ( 14 ) (Figure 1 ).…”
Section: Introductionmentioning
confidence: 97%
“…Changes of the sugar puckering from C2′-endo to C3′-endo, while preserving the anti orientation of the nucleobases, result in the A-form of ds DNA, with deep and narrow major grooves and wide and shallow minor grooves. 1 In contrast to that found for DNA, the A-form is most common in RNA. Changes of the orientation of only the guanine residues from anti to syn of A-form DNA, coiling from right-handed to left-handed, as well as the C3′-endo puckering of the sugar moieties produces the less common Z-form of DNA.…”
Section: ■ Introductionmentioning
confidence: 81%
“…In the most common B-form of double-stranded (ds) DNA, the nucleobases take on an anti orientation and the 2′-deoxyribose sugar moieties exhibit C2′-endo puckering. Changes of the sugar puckering from C2′-endo to C3′-endo, while preserving the anti orientation of the nucleobases, result in the A-form of ds DNA, with deep and narrow major grooves and wide and shallow minor grooves . In contrast to that found for DNA, the A-form is most common in RNA.…”
Section: Introductionmentioning
confidence: 99%
“…For example, experiments exploiting the evolution of a double quantum coherence under the heteronuclear local elds of neighbouring spins have been used to measure the d torsion angles of two 2 0 -deoxynucleosides doubly 13 C-labelled at the C3 0 and C4 0 positions. 24 Similarly, the H1 0 -C1 0 -C6-H6 projection torsion angle dening the relative orientation of the nucleoside pyrimidine and ribose rings in uniformly labelled [ 13 C, 15 N]uridine has been estimated by selective excitation of 13 C double-quantum coherences under MAS at rotational resonance. 25 Rotational echo double resonance (REDOR) is a solid-state NMR technique used to measure dipolar couplings and hence distances between pairs of different nuclear spins, which is frequently applied to biological structure problems.…”
Section: Structure Of Nucleic Acids Componentsmentioning
confidence: 99%